Fast Trabecular Bone Strength Predictions of HR‐pQCT and Individual Trabeculae Segmentation–Based Plate and Rod Finite Element Model Discriminate Postmenopausal Vertebral Fractures. (18th June 2013) - Liu, X Sherry; Wang, Ji; Zhou, Bin; Stein, Emily; Shi, Xiutao; Adams, Mark; Shane, Elizabeth; Guo, X Edward
ABSTRACT Although high‐resolution peripheral quantitative computed tomography (HR‐pQCT) has advanced clinical assessment of trabecular bone microstructure, nonlinear microstructural finite element (µFE) prediction of yield strength using a HR‐pQCT voxel model is impractical for clinical use due to its prohibitively high computational costs. The goal of this study was to develop an efficient HR‐pQCT‐based plate and rod (PR) modeling technique to fill the unmet clinical need for fast bone strength estimation. By using an individual trabecula segmentation (ITS) technique to segment the trabecular structure into individual plates and rods, a patient‐specific PR model was implemented by modeling each trabecular plate with multiple shell elements and each rod with a beam element. To validate this modeling technique, predictions by HR‐pQCT PR model were compared with those of the registered high‐resolution micro–computed tomography (HR‐µCT) voxel model of 19 trabecular subvolumes from human cadaveric tibia samples. Both the Young's modulus and yield strength of HR‐pQCT PR models strongly correlated with those of µCT voxel models (r2 = 0.91 and 0.86). Notably, the HR‐pQCT PR models achieved major reductions in element number (>40‐fold) and computer central processing unit (CPU) time (>1200‐fold). Then, we applied PR model µFE analysis to HR‐pQCT images of 60 postmenopausal women with (n = 30) and without (n = 30) a history of vertebral fracture. HR‐pQCT PR model revealed significantly lower Young's modulus and yield strength at the radius and tibia in fracture subjects compared to controls. Moreover, these mechanical measurements remained significantly lower in fracture subjects at both sites after adjustment for areal bone mineral density (aBMD) T‐score at the ultradistal radius or total hip. In conclusion, we validated a novel HR‐pQCT PR model of human trabecular bone against µCT voxel models and demonstrated its ability to discriminate vertebral fracture status in postmenopausal women. This accurate nonlinear µFE prediction of the HR‐pQCT PR model, which requires only seconds of desktop computer time, has tremendous promise for clinical assessment of bone strength.